Professional Formation of the Future Primary School Teacher by Means of Folk Decorative-Applied Arts - Buchkivska, Galyna (Pedagogical Discourse, 2017)
The article attempts to analyze the influence of means of national culture, in particular folk decorative-applied arts, on the formation of a creative teacher, his or her aesthetic tastes and spiritual-moral values, ethnocultural self-identification and national consciousness. The mechanisms of influence of the content, forms and methods of teaching folk decorative -applied art on the professional training and ethnocultural formation of the personality of the future primary school teacher under the conditions of higher pedagogical educational institution have been revealed. The attention is drawn to the fact that the updating of the content, the improvement of traditional and the use of innovative forms and methods of artistic-labor training of the future primary school teachers, primarily through their involvement in self-expression in artistic-decorative creativity, provides the opportunity to reveal the creative potential and to enrich the ethnocultural experience of the future teachers. The pedagogical conditions of the use of content, forms and methods of training for the purpose of ethnocultural formation of the future teachers of primary classes by means of folk decorative-applied arts in the pedagogical higher educational establishment have been determined. Taking into account the specifics of the preparation of the future primary school teachers, the main groups of teaching methods are distinguished for different types of decorative-applied arts: 1) didactic-organizational, aimed at the organization of mainly reproductive and part-search activity, acquisition of students theoretical knowledge and practical skills of the use of artistic techniques and technologies of materials processing; 2) artistic-creative, which are oriented on creative subject-transformation activity, connected with independent designing and manufacturing of decorative-applied goods according to their own plan.